Analisis Kesalahan Berbahasa pada Karangan Siswa di Era Digital - Sika, Amelia; Nasution, Nur Hakima Akhirani; Sarah, Isma; Harahap, Pitriyanti; Hotmalia, Suzy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze language errors in students’ essays in the digital era using a literature study method. The data sources were obtained from various research articles and academic publications published between 2020 and 2025. The results show that the most common language errors occur in aspects of spelling, morphology, syntax, and semantics. These errors are generally caused by students’ low mastery of Indonesian grammar rules and the influence of digital culture, which encourages the habitual use of informal language in writing. The development of digital technology, on the one hand, provides opportunities for students to easily access learning resources but, on the other hand, presents new challenges for maintaining linguistic accuracy. Therefore, an adaptive Indonesian language learning strategy is required—one that balances digital literacy and proper language use. This study is expected to contribute to improving the effectiveness of writing instruction and fostering students’ awareness of the importance of using correct and standard Indonesian in the modern digital era.